An adaptive multi-biometric incremental fusion strategy in the context of BMEC 2007 - Allano, L.; Garcia-Salicetti, S.; Dorizzi, B. (2008 10th International Conference on Control Automation Robotics and Vision, 2008)
We present the general principles of a dynamical sequential fusion strategy for multibiometric systems allowing reducing the cost associated to the use of different modalities while preserving a good performance compared to that of a global fusion system. We have implemented this strategy in the BMEC (BioSecure multimodal evaluation campaign) 2007 cost-sensitive evaluation. We show that this approach was very robust to the occurrence of missing data thanks to its adaptive implementation.